A glossary of semantics and pragmatics - Cruse, D. A. (Edinburgh University Press, 2006)
This alphabetic guide introduces terms referring to key concepts in semantics and pragmatics. The study of meaning as it is conveyed through language - the domain of semantics and pragmatics - is one of the central concerns of linguistics, and its importance cannot be exaggerated. Written by an author well-known in the field of semantics, the glossary provides clear and accessible explanations of terms drawn from a wide range of theoretical approaches. Key Features: A handy and easily understandable reference book for students beginning the study of semantics or pragmatics Supplies numerous cross-references to related terms Contains an introduction which provides an overview of the field Covers traditional terminology as well as terms relating to more recent approaches, such as Cognitive Semantics Includes an annotated bibliography with suggestions for further reading.
Keywords: Discourse analysis -- Terminology.; Discourse analysis.; Pragmatics -- Terminology.; Pragmatics.; Semantics -- Terminology.; Semantics.; Semantics; Pragmatique -- Terminologie.; Pragmatique.; Sémantique -- Terminologie.; Sémantique.; pragmatics.; semantics.; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Semantics.; LANGUAGE ARTS & DISCIPLINES -- Rhetoric.; Discourse analysis; Pragmatics; Terminology